A high temperature study on thermodynamic, thermal expansion and electrical properties of BaCe0.4Zr0.4Y0.2O3−δ proton conductor - Basbus, Juan Felipe (2016)
BaCe0.4Zr0.4Y0.2O3−δ (BCZY) was synthesized by solid state reaction, calcined and sintered at 1600 °C for 12 h. Crystal structure was studied by X-ray diffraction (XRD). Morphology and porosity were determined by scanning electron microscopy (SEM). Crystalline structure, oxygen non-stoichiometry, linear expansion and electrical conductivity were characterized under oxidizing and reducing atmosphere by high temperature X-ray diffraction (HT-XRD), thermogravimetry (TG), dilatometry, and electrochemical impedance spectroscopy (EIS), respectively. Chemical stability under CO2-rich atmosphere was evaluated by TG. BCZY electrical conductivity was studied by EIS under O2-containing atmosphere with water vapor (2% H2O) and heavy water vapor (2% D2O) in order to evaluate protonic conductivity. Throughout these techniques, interstitial proton incorporation/loss was observed under oxidizing and reducing atmosphere, between 300 and 500 °C. The conductivity presents two contributions. The bulk conductivity at high frequencies takes the same value regardless wet oxidizing or reducing atmosphere, decreasing its value in presence of D2O vapor supporting H-conductivity. On the other hand, the grain boundary conductivity was strongly dependent on the nature of wet atmosphere.